2023
DOI: 10.1590/1518-8345.6364.3894
|View full text |Cite
|
Sign up to set email alerts
|

Professional satisfaction in nursing during the COVID-19 pandemic

Manuela Vilas Boas Pirino,
Carlito Lopes Nascimento Sobrinho,
Ariane Polidoro Dini

Abstract: Objective: to assess the job satisfaction of nursing professionals who worked in care and management during the COVID-19 pandemic. Method: cross-sectional epidemiological study, with the participation of 334 nursing professionals of a teaching hospital. Absolute and relative frequencies of qualitative variables and means of numerical variables were calculated. The mean scores of the domains of the Job Satisfaction Survey were compared with sociodemographic-labor variables. Student’s t-test, Mann-Whitney test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…showed that remuneration, benefits and conditions for promotions emerged as some of the main factors of job dissatisfaction (31) .…”
Section: Discussionmentioning
confidence: 99%
“…showed that remuneration, benefits and conditions for promotions emerged as some of the main factors of job dissatisfaction (31) .…”
Section: Discussionmentioning
confidence: 99%